Discoursing Women’s Political Participation Towards Achieving Sustainable Development: The Case of Women in Parti Islam Se-Malaysia (PAS) - Zaireeni Azmi (Kajian Malaysia, 2020)
Malaysia has been committed to meet its commitments to the Sustainable Development Goals (SDGs) by 2030. One of the goals is to achieve gender equality. However, in Malaysia, the Global Gender Gap Index which measures gender disparities in economic participation and opportunities, education attainment, health and political empowerment reported that Malaysia ranked at 111 out of 145 countries in 2016. It has fallen far from its overall ranking of 72 in 2006. In terms of political participation, the low score in politics is because of the lack of women in leadership and decision-making positions that dragged down Malaysia’s index even though Malaysia had set a target for women to fill 30% or more in decision-making positions. In the recent 14th general election, a total of 252 female candidates named out of the 2,333 parliament and state seats resulted in only 92 female elected representatives. This article provides an overview of women’s political participation focusing on members of Parti Islam Se-Malaysia (PAS). There were 30 female respondents interviewed and they were recruited from the two states in Malaysia namely Selangor and Kelantan. It analyses the reasons for women’s missing presence at the decision-making level in the party and at national level which contributed to Malaysia’s slow achievement of the SDGs. This article will discuss how PAS’s organisational structure and women’s preference will impose challenges towards achieving SDG 5. Women themselves determine the level of participation and contributions that they are willing to play in politics.